Inspirational Learning Assistance as an Effort to Enhance the Learning Motivation of Students at MTs Nurul Qolbi - Puja Khaerunnisa; Enan Kusnandar; Dyah Wulandari (Yayasan Daarul Huda Kruengmane, 2026)
This community service activity was conducted as an effort to provide assistance to students of MTs Nurul Qolbi in improving their learning motivation through inspirational learning mentorship. The background of this activity is the still low level of students’ learning motivation, which has an impact on the lack of clarity in their educational goals. The objective of this community service activity is to increase students’ learning motivation. The implementation method used a Participatory Action Research (PAR) approach. The results of the activity indicate that some students did not yet have strong learning motivation and did not fully understand the importance of education for their future. Through inspirational learning mentorship activities, students began to express their interests, learning obstacles, and expectations, resulting in a higher level of learning motivation compared to before.